The trends and hotspots of immunotherapy for metastatic colorectal cancer from 2013 to 2022: A bibliometric and visual analysis - Yifan Gong; Jianping Kang; Mingting Wang; Firdaus Hayati; Syed Sharizman Syed Abdul Rahim; Lucky Poh Wah Goh (Human Vaccines & Immunotherapeutics)
An increasing body of research indicates that immunotherapy has demonstrated substantial effectiveness in the realm of metastatic colorectal cancer(mCRC), especially among patients with deficient mismatch repair (dMMR) or microsatellite instability-high (MSI-H) (dMMR/MSI-H mCRC). This study constitutes the inaugural bibliometric and visual analysis of immunotherapy related to mCRC during the last decade. Between 2013 and the conclusion of 2022, we screened 306 articles from Web of Science and subjected them to analysis using CiteSpace and VOSviewer. The United States stood out as the primary contributor in this area, representing 33.33% of the publications, with China following closely at 24.51%. The most prolific institution has the lowest average citation rate. Sorbonne University were the most highly cited institutions. Notably, Frontiers In Oncology published the largest quantity of articles. Andre, Thierry, and Overman, Michael J. were prominent authors known for their prolific output and the high citation rates of their work. The focus areas in this field encompass “tumor microenvironment,” “liver metastasis,” “tumor-associated macrophages,” “combination therapy” and “gut microbiota.” Some keywords offer promise as potential biomarkers for evaluating the effectiveness of immunotherapeutic interventions.